Volume 9: Ocean Renewable Energy 2015
DOI: 10.1115/omae2015-42056
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modelling of Fixed Oscillating Water Column Wave Energy Conversion Devices: Toward Geometry Hydraulic Optimization

Abstract: The Oscillating Water Column (OWC) is one of the simplest and most studied concepts for wave energy conversion. The commercial scale diffusion of the OWC technology is, however, strongly dependent upon the device optimization. Research at a fundamental level is therefore still required. Analytical, numerical and experimental models are necessary tools for advancing in the knowledge of the system and thus promoting its passage at the commercial level. In this work, a simplified frequency domain rigid piston mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…In recent work with OpenFOAM and IHFOAM, it was also observed that the pressure in the numerical model was slightly over-predicted [22] when RANS equations were solved. On the other hand, when a LES model was used, the numerically predicted pressure was closer to the experimentally measured pressure [35]. In other studies, the correlation between the experimental and the numerical results is similar to the present study, however the pressure fluctuations were 80 Pa [22], 180 Pa [18], 200 Pa [35] and 900 Pa [19], which are significantly smaller in comparison to 1400 Pa which is observed here.…”
Section: Regular Wavesupporting
confidence: 88%
See 2 more Smart Citations
“…In recent work with OpenFOAM and IHFOAM, it was also observed that the pressure in the numerical model was slightly over-predicted [22] when RANS equations were solved. On the other hand, when a LES model was used, the numerically predicted pressure was closer to the experimentally measured pressure [35]. In other studies, the correlation between the experimental and the numerical results is similar to the present study, however the pressure fluctuations were 80 Pa [22], 180 Pa [18], 200 Pa [35] and 900 Pa [19], which are significantly smaller in comparison to 1400 Pa which is observed here.…”
Section: Regular Wavesupporting
confidence: 88%
“…On the other hand, when a LES model was used, the numerically predicted pressure was closer to the experimentally measured pressure [35]. In other studies, the correlation between the experimental and the numerical results is similar to the present study, however the pressure fluctuations were 80 Pa [22], 180 Pa [18], 200 Pa [35] and 900 Pa [19], which are significantly smaller in comparison to 1400 Pa which is observed here. The reason for the high pressure is the high damping induced from the small orifice in combination with the high waves.…”
Section: Regular Wavesupporting
confidence: 88%
See 1 more Smart Citation
“…Given through use of long-term metocean condition, response of the turbines can be tuned to H m0 ≤ 3.5 m. Even with this small configuration change, it is expected that the performance can be increased to 40-50% by adapting the turbine operation to the local conditions [47], usually done by CFD modeling that has shown the improvements that an OWC can attain [56,57]. However, such an effort is outside of the scope for this paper, whose primary focus is to quantify the resource, energy and economic potential.…”
Section: Discussionmentioning
confidence: 99%
“…Through the coupling of multi-model nesting, energy analysis and utilising a non-optimised WEC solution, ratios are proposed for which an investment would be feasible. Past studies indicated the possibility of tuning the converter behaviour to local condition, hence scaling its performance is expected to increase the energy production by at least 50% [47,56,59]. An integrated breakwater OWC operates at shallow water areas where surge and depth breaking will be more dominated, and thus simple Froude scaling is not possible.…”
Section: Discussionmentioning
confidence: 99%